The caliphate at war: the ideological, organisational and military innovations of Islamic State - Hashim, Ahmed (Hurst & Company, 2018)
ISIS’s astonishing and unexpected military victories in 2014 and 2015 redrew the geopolitical map of the Middle East. Media attention focused on the organisation’s savage treatment of its enemies and its ability to attract foreign fighters, but as this dispassionate book demonstrates it also made important innovations in strategy, ideology and governance. Ahmed S. Hashim argues that by focusing their ideology first and foremost on extreme anti-Shia sectarianism — rather than on Western ‘infidels’ — ISIS’ founders were able to present themselves as the saviours of what they saw as the embattled Sunni ‘nation’ in Iraq. This enabled them to win the support of Sunni communities. Moreover, ISIS’ stunning ability to take major cities was a result of its innovative tactics. It sowed terror in advance of its attacks by using targeted assassinations to kill key city leaders, and its decentralised regional command structure facilitated an unusual degree of coordination between small assault units. At the same time the organisation made a serious effort to engage in state-building and population control. By going beyond the often starkly unpleasant current affairs of the Islamic State, The Caliphate at War undertakes an essential investigation into the successes of the group, to better understand how the movement has survived, thrived, and reshaped the Middle East.